ANALISIS IMPLEMENTASI KEBIJAKAN MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) DI PERGURUAN TINGGI PADA MASA PANDEMI COVID 19 - Nailurrohmah Khoiri; Sutrisno Sutrisno (Irfani (e-Journal), 2023)
Abstract Digital transformation, which is developing so rapidly in the world of education, requires educators and students to utilize technology in the learning process. Various efforts have been made by the government to face the era of technological advances, one of which is in the world of higher education by enforcing the Merdeka Learn Kampus Merdeka (MBKM) policy. However, due to face-to-face restrictions as a result of the Covid-19 pandemic, there are bound to be obstacles in its implementation. By using the Systematic Literature Review (SLR) method to study and analyze journals that discuss MBKM policies, the results show that the implementation of MBKM in both PTS, PTN, and PTKIN is not balanced with the program objectives that have been formulated. There were several obstacles in its implementation, especially both before Covid-19 and during Covid-19 which had an impact on the quality of university graduates. Therefore, there is a need for balanced coordination between the government, universities, partners and students. So that the programs planned are in accordance with the ability of PT in facilitating students, the readiness of students in implementing the program, the needs of partner companies/industries and in accordance with the goals formulated by the government.